2006
DOI: 10.3758/bf03192765
|View full text |Cite
|
Sign up to set email alerts
|

Cyberball: A program for use in research on interpersonal ostracism and acceptance

Abstract: Since the mid-1990s, research on interpersonal acceptance and exclusion has proliferated, and several paradigms have evolved that vary in their efficiency, context specificity, and strength. This article describes one such paradigm, Cyberball, which is an ostensibly online ball-tossing game that participants believe they are playing with two or three others. In fact, the "others" are controlled by the programmer. The course and speed of the game, the frequency of inclusion, player information, and iconic repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
649
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 823 publications
(672 citation statements)
references
References 7 publications
17
649
1
5
Order By: Relevance
“…Participants were thus asked to play the Cyberball game (Williams et al 2000; Williams and Jarvis 2006), a virtual ball tossing game that induces social exclusion in a highly 8 standardized manner. In this paradigm, participants were led to believe that they were playing over the internet with two other people who are taking part in similar experiments but who are, in fact, computer generated (see (Williams and Jarvis 2006) for a complete description).…”
Section: Figure 1 Near Here Proceduresmentioning
confidence: 99%
“…Participants were thus asked to play the Cyberball game (Williams et al 2000; Williams and Jarvis 2006), a virtual ball tossing game that induces social exclusion in a highly 8 standardized manner. In this paradigm, participants were led to believe that they were playing over the internet with two other people who are taking part in similar experiments but who are, in fact, computer generated (see (Williams and Jarvis 2006) for a complete description).…”
Section: Figure 1 Near Here Proceduresmentioning
confidence: 99%
“…fMRI scans were obtained while participants completed the Cyberball task (27). Participants were told they would be playing a virtual balltossing game with two other individuals.…”
Section: Methodsmentioning
confidence: 99%
“…To quantify the magnitude of participants' inflammatory response to this stressor, we collected oral fluids during the stressor and assessed two key markers of inflammatory activity-namely, a soluble receptor for tumor necrosis factor-α (sTNFαRII) and interleukin-6 (IL-6). In a subsequent session, a subset of these participants (n = 31) was scanned while they played a computerized ball-tossing game called "Cyberball" (27), in which participants were ultimately excluded by two other supposed players, leading to an experience of social rejection. We then examined how differences in neural activity during social rejection correlated with differences in inflammatory responses to the TSST.…”
mentioning
confidence: 99%
“…These children were subsequently invited to participate in an fMRI study, when these children were on average 14 years of age. In the fMRI, the adolescents with a history of chronic rejection or stable acceptance during elementary school were subjected to Cyberball social exclusion/inclusion (Williams & Jarvis, 2006). The results showed that rejected children compared to accepted children showed heightened activation of the dorsal anterior cingulate cortex (dACC) during social exclusion.…”
Section: Relationships With Peers and Executive Function Developmentmentioning
confidence: 99%